O professor na visão das crianças: uma pesquisa sobre a construção do conhecimento social sob o enfoque piagetiano - Guimarães, Taislene; Saravali, Eliane Giachetto [UNESP] (My University, 2010)
The focus of this paper is on the construction of social knowledge according to Piagetian constructivist theory. We present data related to the ideas of children aged seven and eight years old about the role of the teacher. We observed 52 children, both male and female, immersed in two different educative environments: one considered socio-moral constructivist and the other one, traditional. The main results showed the particular processes of the individuals when they try to comprehend the surrounding reality. The only meaningful difference between the two environments studied was related to the comprehension of the necessity of formation to develop the function of a teacher. In the other aspects observed we have not found meaningful differences concerning the representations of the subjects as well as the environment in which they participated.

No presente trabalho, enfocamos a construção do conhecimento social segundo o referencial construtivista piagetiano. São apresentados dados referentes às ideias de crianças entre 7 e 8 anos sobre o papel do professor. Trabalhamos com 52 sujeitos, de ambos os sexos, inseridos em ambientes educativos distintos: um ambiente considerado sócio-moral construtivista e um ambiente tradicional. Os principais resultados mostraram os processos peculiares percorridos pelos indivíduos na tentativa de compreensão da realidade social que os cerca. Só houve diferença significativa entre os ambientes pesquisados no que se refere à compreensão sobre a necessidade de formação para o exercício da função de professor. Nos demais aspectos pesquisados, não foram encontradas diferenças significativas em relação às representações dos sujeitos e os ambientes educacionais do qual faziam parte.
The teacher under children’s view: a research on the construction of social knowledge under piagetian theory